Variations in management accounting practices: explanatory factors / Ahmed Abdullah Saad Al-Dhubaibi …[et al.] - Al-Dhubaibi, Ahmed Abdullah Saad; Abdul Rahman, Ibrahim Kamal; Haniff, Mohd Nizal; Mohd Sanusi, Zuraidah (Universiti Teknologi MARA Cawangan Selangor, 2015)
Variations in the management accounting practices (MAPs) of firms are evident. Many studies have observed various levels of MAP adoption and implementation, especially in developing countries. Surveys on MAP in developing countries have reported wide variations in such practices, with traditional MAP being more popular than advanced MAP despite the advantages of the latter, as suggested by academicians and practitioners. This study investigates several factors that may explain the variations in the MAPs of firms in Yemen and highlights the role of firm owners and personnel in deciding and selecting the MAPs in their respective firms. Firms that operate in the various economic sectors of Yemen are included in the sample. The International Federation of Accountants (IFAC) framework on management accounting evolution is used to classify the MAP level of advancement. The ownership of firms, industry type, and educational level of Chief Financial Officers (CFOs) significantly explain the variations in the MAPs of firms in Yemen. Foreign ownership and highly educated CFOs can drive firms to adopt a more sophisticated MAP. Industry type also has a significant role in determining the level of MAP advancement. Interestingly, the MAP advancement level in the financial and banking sector is higher than that in other economic sectors, with natural resources-extracting firms demonstrating the second-highest MAP advancement level. These results improve our understanding of why some firms invest in upgrading their management accounting systems and targeting the best practices, while others tend to maintain their use of traditional MAPs.